Tools supporting the process of knowledge management and economic security in the organization - Wyrębek, Henryk (Management and Administration Journal, 2023)
Knowledge management is a widely recognized discipline and specific part of the overall management science. However, the concept is characterized by great diversity, it has no single dominant approach by the speaker on how to manage knowledge and understanding of generally recog-nized object management, which is knowledge. In addition, there are also different examples of essence of knowledge management. It can be assumed that the information, knowledge and competen-cies within a given unit of time, combining strategic contradictions and exploiting existing intellectual capital are the basic assumptions to build a competitive advantage in the management of economic security. This article presents some of the tools supporting the process of economic security management, and from the empirical knowledge management tools used in the enterprise. Undertaken to investigate the following problem: whether knowledge management tools can be used in the management of economic security? To investigate the given problem in the enterprise a diagnostic survey method was used.